University insiders' perceptions of doctoral education development in five East and Southeast Asian countries: An institutional logics perspective. (27th June 2022) - Zhuang, Tengteng; Liu, Baocun; Ding, Ruichang
Abstract: This article reports on a study that analysed multiple logics behind the development of doctoral education in China, Japan, South Korea, Singapore and Thailand. The analysis focused on the development over the past two decades and general measures to ensure quality. Research materials analysed in this article consisted of semi‐structured interviews with insiders in the doctoral education system in each of the five countries. The findings reveal that the growth of the doctoral education sector in China follows state logic, profession logic and corporation logic . Doctoral education in Japan shows state logic, profession logic and market logic . State logic, market logic and corporation logic are manifested in South Korea's doctoral education sector, whereas state logic and profession logic are prominent in Singapore. Doctoral education in Thailand mostly follows state logic and market logic . Establishing and completing the external and internal quality mechanisms, tightening quality inspection procedures and raising requirements for students are common measures put in place for quality assurance throughout East and Southeast Asia.